2022
DOI: 10.1371/journal.pone.0265515
|View full text |Cite|
|
Sign up to set email alerts
|

The helix of CO2, household income, and oil pricing under the assumption of Keynesian consumption function: A policy-mix scenario of oil-importing South Asia for SDGs-2030

Abstract: The purpose of this study is to explore energy prices and their impact on household consumption under the condition of Keynesian consumption theory in South Asian countries over the 1995–2020 periods. By employing the panel ordinary least square model estimation technique, the study attempted to find the relationship between household income and consumption under the theory of Keynesian consumption function. Furthermore, we investigated the relationship between household consumption and environmental sustainab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Past study of Abbas et al (2020) documented that numerous past studies discovered the well-being effect of increasing energy prices like for several economies and find out that consumers were harmfully affected by the surge in oil prices. However, the recent study of Gang et al (2022) discussed that few number of studies have been found for South Asia countries that considered the well-being price of energy consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Past study of Abbas et al (2020) documented that numerous past studies discovered the well-being effect of increasing energy prices like for several economies and find out that consumers were harmfully affected by the surge in oil prices. However, the recent study of Gang et al (2022) discussed that few number of studies have been found for South Asia countries that considered the well-being price of energy consumption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The PLOS ONE Editors retract this article [ 1 ] because it was identified as one of a series of submissions for which we have concerns about authorship, competing interests, and peer review. We regret that the issues were not addressed prior to the article’s publication.…”
mentioning
confidence: 99%